The 2nd XoveTIC Conference (XoveTIC 2019) 2019
DOI: 10.3390/proceedings2019021031
|View full text |Cite
|
Sign up to set email alerts
|

Dataset for the Aesthetic Value Automatic Prediction

Abstract: One of the most relevant issue in the prediction and classification of the aesthetic value of an image is the sample set used to train and validate the computational system. In this document the limitations found in different datasets used to classificate and predict aesthetic values are exposed, and a new dataset is proposed with images from the DPChallenge.com portal, with evaluations of three different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…After analyzing the degree of generalization of some datasets used in automatic image prediction, it was concluded that it was not enough to consider them as a reference in the training of automatic image prediction and classification systems. Taking this into account, a new set of images from the web portal DPChallenge.com was developed in search of greater statistical consistency [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the degree of generalization of some datasets used in automatic image prediction, it was concluded that it was not enough to consider them as a reference in the training of automatic image prediction and classification systems. Taking this into account, a new set of images from the web portal DPChallenge.com was developed in search of greater statistical consistency [7].…”
Section: Methodsmentioning
confidence: 99%
“…In this case, unlike other image quality assessment algorithms that use synthetically distorted images [3,4], it was decided to use images with absence of distortion [5,6]. Despite the fact that the data collected contained quality and aesthetic results, on this occasion only the quality data were used as they constituted more objective results [7].…”
Section: Introductionmentioning
confidence: 99%